2010
DOI: 10.4081/ijas.2010.e10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chia (Salvia hispanica L.) seed supplementation on rabbit meat quality, oxidative stability and sensory traits

Abstract: Chia (Salvia hispanica L.) seed (SHS) dietary supplementation is effective in improving the nutritional quality of rabbit meat for consumers and could contribute to the novel concept of “functional food” in human nutrition. A trial has been conducted in order to verify the effects of three levels (0, 10, or 15%) of SHS inclusion in a rabbit diet on the meat quality, oxidative stability and sensory traits. The dietary treatment did not induce any differences in the ultimate pH, chemical composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 30 publications
6
29
1
6
Order By: Relevance
“…These results are in agreement with Meineri et al (2010), who founds a dose-dependent increase in C18:2 (n-6) and C18:3 (n-3) in rabbits whose feed was supplemented with seeds of Salvia hispanica. Even Jung et al (2010) found a reduction in SFA and monounsaturated fatty acid (MUFA) and an increase in PUFA content in broiler breast after feed was supplemented with a mixture of polyphenols (gallic acid) and linoleic acid.…”
Section: Fatty Acid Composition Of Meatsupporting
confidence: 82%
“…These results are in agreement with Meineri et al (2010), who founds a dose-dependent increase in C18:2 (n-6) and C18:3 (n-3) in rabbits whose feed was supplemented with seeds of Salvia hispanica. Even Jung et al (2010) found a reduction in SFA and monounsaturated fatty acid (MUFA) and an increase in PUFA content in broiler breast after feed was supplemented with a mixture of polyphenols (gallic acid) and linoleic acid.…”
Section: Fatty Acid Composition Of Meatsupporting
confidence: 82%
“…Los valores de humedad obtenidos son similares a los reportados por Gašperlin et al (24), para animales entre 77 y 90 días, con porcentajes alrededor de 72.7% para el mismo músculo; y son un poco más bajos que la mayoría de los reportes con valores aproximados de 74.30% (25), 74.36% (26) 75.07% (7), 75.56% (27). Entre los estudios más recientes se puede destacar el de Meineri et al (25), quienes utilizaron las semillas de chía (Salvia hispanica L.) como suplemento de las dietas, en 10% y 15%, obteniéndose carnes con calidad similar al control. Simonová et al (7) obtuvieron resultados parecidos al utilizar una suplementación con fitoaditivos tales como orégano.…”
Section: Discussionunclassified
“…De acuerdo a los resultados de la tabla 3, los valores de cenizas obtenidos en este estudio superan la gran mayoría de los reportes más recientes de algunos autores, quienes encontraron contenidos entre 1.07 y 1.43% (7,25,26). Las cenizas representan el contenido relativo de minerales que pueden incluir cualquiera de los iones esenciales para los humanos; haciendo posible decir, que las carnes de la presente investigación tienen un aporte nutricional suficiente con respecto al suministro de minerales.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…dla kurczaków w celu zwiększenia ilości kwasów omega-3 i omega-6 w jajach, a jednocześnie zmniejszenia kwasu palmitynowego w mięsie lub jako dodatek do pasz dla trzody chlewnej i kró-lików, aby zwiększyć ilość kwasów wielonienasyconych w mięsie oraz poprawić jego walory smakowe [27,28].…”
unclassified